2021
DOI: 10.1021/acs.orglett.1c00766
|View full text |Cite
|
Sign up to set email alerts
|

Photo-oxidative Ruthenium(II)-Catalyzed Formal [3 + 2] Heterocyclization of Thioamides to Thiadiazoles

Abstract: An operationally simple and sustainable one-pot photo-oxidative formal [3 + 2] heterocyclization of β-ketothioamides with aryldiazonium salts catalyzed by Ru­(bpy)3Cl2 has been realized to provide 2,4-disubstituted 5-imino-1,2,3-thiadiazoles in good to high yields under mild reaction conditions for the first time. The reaction proceeded via an α-phenylhydrazone adduct of thioamides leading to 1,2,3-thiadiazoles via N–S bond formation at room temperature. Notably, the products possess Z-stereochemistry with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Our group has concentrated on transformation of ketothioamides (KTAs) to various heterocyclic scaffolds . Recently, a Ru­(II)-catalyzed photo-oxidative protocol for the synthesis 1,2,3-thiadiazoles from the α-phenylhydrazone adduct of KTAs was reported by our group . During the mechanistic investigation of the Ru­(II)-catalyzed photo-oxidative protocol, we found that the oxidative potentials of α-phenylhydrazone adducts are much lower ( E ox = 0.72 and 0.95 V); hence, it could be easy to oxidize them at the anode without any external support.…”
Section: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group has concentrated on transformation of ketothioamides (KTAs) to various heterocyclic scaffolds . Recently, a Ru­(II)-catalyzed photo-oxidative protocol for the synthesis 1,2,3-thiadiazoles from the α-phenylhydrazone adduct of KTAs was reported by our group . During the mechanistic investigation of the Ru­(II)-catalyzed photo-oxidative protocol, we found that the oxidative potentials of α-phenylhydrazone adducts are much lower ( E ox = 0.72 and 0.95 V); hence, it could be easy to oxidize them at the anode without any external support.…”
Section: Results and Discussionmentioning
confidence: 99%
“…19 Recently, a Ru(II)-catalyzed photo-oxidative protocol for the synthesis 1,2,3-thiadiazoles from the α-phenylhydrazone adduct of KTAs was reported by our group. 20 During the mechanistic investigation of the Ru(II)-catalyzed photo-oxidative protocol, we found that the oxidative potentials of α-phenylhydrazone adducts are much lower (E ox = 0.72 and 0.95 V); hence, it could be easy to oxidize them at the anode without any external support. Keeping in mind the importance and reactivity of hydrazones and as part of our ongoing research to develop an efficient synthetic protocol for thiadiazoles, herein, we report a reagent-less electro-oxidative protocol for the synthesis of 28 fully substituted 1,2,3-thiadiazoles from αphenylhydrazone adducts of KTAs at room temperature (Scheme 1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations